SECURING WEB APPLICATIONS WITH OWASP ZAP FOR COMPREHENSIVE SECURITY TESTING - S. P. Maniraj; Chitra Sabapathy Ranganathan; Satheeshkumar Sekar (International Journal of Advances in Signal and Image Sciences)
The powerful Open Web Application Security Project (OWASP)-Zed Attack Proxy (ZAP) tool secures web applications with extensive security testing. Its main goal is to find and fix web application vulnerabilities before they can be exploited. The goal is to improve web application security using OWASP ZAP scans and inspections. Simulating SQL injection and cross-site scripting attacks using the tool reveals an application's security flaws. OWASP ZAP automates testing to protect sensitive data and web application integrity. The purpose is to protect online applications from attacks to reduce security breaches and ensure industry compliance. Modern online applications' security and dependability depend on OWASP ZAP's systematic vulnerability discovery and mitigation. By enhancing scan performance and providing actionable security information, the experimental results show that the OWASP ZAP helps safeguard online applications and reduce the danger of cyberattacks. The objective is to enhance its skills to provide comprehensive, prompt, dependable security evaluations across various situations.